Kajian Tertib Administrasi Pertanahan Tanah Kasultanan dan Tanah Kadipaten Setelah Berlakunya Perdais Yogyakarta - Vani Wirawan (Jurnal Ilmiah Penegakan Hukum, 2019)
The writing of this law aims to review and analyze the orderly administration of land to the Sultanate Land (SG) and the Duchy Land (PAG) after the enactment of the Yogyakarta Special Region Law, and the current pattern of management and utilization of the Sultanate and Duchy Land based on regional land policies in the context of creating welfare Public. The legal research writing method used is normative legal research using the law approach and sociological approach. The results of the study can be summarized as follows: First, that the results have occurred TSM Land Administration in Discipline and sustainability is seen from the number of Sultan Ground (SG) and Pakualaman Ground (PAG) that have been issued as many as 3,766 certificates from a total of 13,944 fields spread throughout the DIY Region. Second, the current pattern of management and utilization of the Sultanate of Land (SG) in DIY is legally formally managed by Panitikismo as a manifestation of the container / body that deals with, manages, and utilizes SG Ngayogyakarta Sultanate, based on Law Number 3 of 1950 concerning the Establishment of DIY and emphasized by DIY Perdais Number 1 of 2017 concerning Management and Utilization of Sultanate Land and Duchy Land. For the Duchy Land (PAG) management, control and utilization must obtain permission from the Pakualaman Duchy.